Cultura organizacional e rede social: um estudo em empresas de presta????o de servi??os de contabilidade - Silva, In??s Francisca Neves (2015)
Through the character of an exploratory analysis, this paper aims to understand, through current and desirable values, organizational cultures as well as the configuration of the social network and its relation to culture in financial services companies in the cities of Tr??s Lagoas-MS and Campo Grande-MS. It is a quantitative study, being two companies from Tr??s Lagoas and two from Campo Grande, and for that ,we used three questionnaires developed by Nelson (2006): The Personal Value Profile ,which seeks to know the values of each individual belonging to the organization, the Aggregate Value Profile which, through the perception of employees, raises the current organizational values and the desired ones , and a questionnaire of social networks, which seeks, within the organization, verbal contacts that take place between employees. The second one was structured with 20 statements, subdivided into 4 sets of 4, using a priority scale ranging from 1 to 4. Through the analysis, it was found that the current organizational culture of S2, R and S3 companies behaves homogeneously, i.e. ,the values are perceived by employees more similarly. Regarding the desired culture, only in the S2 company there would be, in the perception of employees, a change in culture; in R and S3 companies, employees said they would not alter that culture. In the S1 company, a heterogeneous culture was found and employees also want changes in culture. As for the social network, it was observed that S1 and S2 companies are present in the form of great center, being less peripherical, while in R and S3 companies, the center is located very close to the periphery in relation to size, and S2 was the company with the highest distinction. When the values are related to the social network with a view to find a connection in the transmission of values through the network, it was found that the network does not interfere with the formation of the organizational culture. A result that drew attention was about the culture regarding the location of the companies. In companies located in the capital, whose owners are people with no degree of kinship, the current organizational culture was homogeneous and there was not desire to change it. But in the companies of the so-called "inner cities", whose owners have a strong degree of kinship, the cultures are different and there is a desire for change on the part of employees, contrary to what would be expected.